Genetics studies indicate that neural induction and early neuronal maturation are disturbed in autism - Casanova, Emily L.; Casanova, Manuel F. (Frontiers in Cellular Neuroscience, 2014)
Postmortem neuropathological studies of autism consistently reveal distinctive types of malformations, including cortical dysplasias, heterotopias, and various neuronomorphometric abnormalities. In keeping with these observations, we review here that 88% of high-risk genes for autism influence neural induction and early maturation of the neuroblast. In addition, 80% of these same genes influence later stages of differentiation, including neurite and synapse development, suggesting that these gene products exhibit long-lasting developmental effects on cell development as well as extensive functional redundancy in processes of neural proliferation, growth, and maturation. We also address the putative genetic overlap of autism with conditions like epilepsy and schizophrenia, with implications to shared and divergent etiologies. This review imports the necessity of a frameshift in our understanding of the neurodevelopmental basis of autism to include all stages of neuronal maturation, ranging from neural induction to synaptogenesis.